Microscopic Identification, Phytochemical Analysis, and Study of Antioxidant Properties of Branches, Leaves, and Fruits of Kazakh Medicine Sambucus sibirica - Pengyan Yan; Shuak Halimubek; Jingjing Chen; Wenhuan Ding; Sien Fan; Dongdong Wang; Xiaoqing Zhang; Haiyan Xu; Xuejia Zhang (Molecules)
Sambucus sibirica, a deciduous shrub from the Adoxaceae family, is a traditional Kazakh medicine used in Xinjiang, China. Its branches, leaves, and fruits are used to treat fractures, rheumatoid arthritis, and nephritis. To advance research on S. sibirica, we conducted studies on its microscopic identification, chemical composition, and biological activity. The cross-sectional features of the branches, leaves, and fruits were observed under a microscope, revealing different types of ducts, cork cells, non-glandular hairs, oil droplets, stone cells, scale hairs, and star-shaped hairs in the S. sibirica powders. Fourier transform infrared spectroscopy (FTIR) was used to characterize the presence of specific chemical groups, revealing similarities and differences between different parts. Thin-layer chromatography (TLC) confirmed that chlorogenic acid was present in the branches, leaves, and fruits, whereas rutin was more prominent in the leaves. The total flavonoid contents were determined by a photocolorimetric approach and resulted in values of 7419.80, 5193.10, and 3629.10 μg·g−1 (dry weight) for the leaves, branches, and fruits, respectively. Further qualitative and quantitative analyses via ultra-performance liquid chromatography coupled with triple quadrupole tandem mass spectrometry (UPLC-QqQ-MS/MS) identified rutin, chlorogenic acid, quercetin, isoquercetin, and astragalin, with contents ranging from 1.00 to 4535.60 μg·g−1 (dry weight). Antioxidant tests revealed that the branches, leaves, and fruits of S. sibirica presented antioxidant properties, with the leaves demonstrating the highest activity, followed by the branches and fruits. These results align with the results of the quantitative analysis. This study provides valuable insights into the microscopic features, chemical composition, and antioxidant activity of S. sibirica, laying the foundation for its pharmacognosy research and quality standards and offering a reference for its future development and utilization.